Combinations of Ethers and B(C6F5)3 Function as Hydrogenation Catalysts1. Issue 29 (14th June 2013) - Hounjet, Lindsay J.; Bannwarth, Christoph; Garon, Christian N.; Caputo, Christopher B.; Grimme, Stefan; Stephan, Douglas W.
<x xml:space="preserve">Abstract</x> It works ether way: Labile adducts of dialkyl ethers with the electrophilic borane B(C6F5)3 are shown to scramble HD to H2 and D2 and catalyze the hydrogenation of 1, 1‐diphenylethylene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>